Big but weak: how many pathogenic genes does human herpesvirus-8 need to cause Kaposi's sarcoma? (Review). - Stürzl, Michael; Ensoli, Barbara (International Journal of Oncology, 1999)
Human herpesvirus-8 (HHV-8) is implicated in the pathogenesis of Kaposi's sarcoma (KS). In the last two years several HHV-8 gene products were heralded to 'cause KS' without any evidence that the respective gene is expressed in the tumor cells of KS lesions. In this framework it is of interest that almost 10% of the genes encoded by HHV-8 have been suggested to promote KS development due to either mitogenic, anti-apoptotic, chemoattractive, angiogenic or transforming activities. The rapidly growing number of HHV-8-encoded genes with 'KS causing' activities raises the question of why HHV-8 may need so many genes to trigger growth of KS that appears to be more closely related to a hyperplasia than to a real sarcoma. In this review an overview of the current knowledge of HHV-8 gene expressions in KS lesions in vivo is presented.